Riconciliazione e perdono: esperienze di misericordia tra Oriente e Occidente - Giuliano, Salvatore (Alpha Omega, 2015)
Summary: In the context of the study of comparative religion, undertaking a comparison of the need which exists in the human being for reconciliation and forgiveness seems to be an impossibility, if we think of how much the concepts of sin, forgiveness and reconciliation are understood in the different doctrinal systems of East and West. The need to expiate our sins arises alongside the need of every human being for religion. Each one understands the need to specify his or her own sins in order to free themselves of them and to escape the damaging effects which those sins bring with them. Starting from this continual chain of moral pacification, which human beings have always invoked, we will try to reach a horizon that is shared by the Abrahamic religions and Eastern religions. The aim is that, during the Jubilee of mercy which is now drawing close, all religions may rediscover the way of forgiveness, in order to overcome the various forms of fundamentalism and intolerance which are tearing humanity asunder, committing themselves to building a world that is a home to everyone, in which we may all at last be able to live in peace.Key words: mercy, forgiveness, reconciliation, religions, sin.Parole chiave: misericordia, perdono, riconciliazione, religioni, peccato.